Pharmacist‐assisted prescribing in an Australian hospital: a qualitative study of hospital medical officers' and nursing staff perspectives. (5th December 2021) - Tran, Tim; Taylor, Simone E.; George, Johnson; Chan, Vincent; Mitri, Elise; Elliott, Rohan A.
Abstract: Background: Pharmacist‐assisted prescribing (also known as pharmacist charting) has been adopted widely across Australia. The perspectives of medical and nursing staff, however, is poorly understood. Aim: To explore the perceived benefits and drawbacks of pharmacist‐assisted prescribing on admission and discharge, from the perspective of hospital medical officers (HMOs) and nurses. Methods: Face‐to‐face, semi‐structured interviews were conducted with orthopaedic junior HMOs, the orthogeriatric HMO and nurses during a study evaluating pharmacist‐assisted prescribing in an orthopaedic unit. Participants were individually interviewed to explore the perceived impacts of pharmacist‐assisted prescribing on patient safety, workflow and HMO skill development. Interviews were audio‐recorded and verbatim transcriptions were analysed independently by two investigators using a simple thematic analysis. Results: Interviews were conducted with six HMOs and six nurses. Emergent themes highlighted various factors which may affect the ability of HMOs to prescribe medications accurately and in a timely manner when there is no pharmacist assisting with prescribing, and the impact of pharmacist‐assisted prescribing on patient flow, safety and staff workload. Participants felt that having a pharmacist assist with prescribing improved patient safety by reducing prescribing errors and admission charting delays, and assisted with patient flow by reducing delays in discharging patients. Participants felt that pharmacist‐assisted prescribing reduced their workload. They noted a drawback was the potential to de‐skill HMOs, but felt this was outweighed by the benefits. Conclusions: Hospital medical officers and nurses reported that pharmacist‐assisted prescribing had benefits on patient safety, patient flow and workload and that these outweigh the potential drawbacks of potentially de‐skilling junior HMOs.